2015
DOI: 10.1080/17461391.2015.1120781
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of poor sleep quality, sleepiness and obstructive sleep apnoea risk factors in athletes

Abstract: These findings suggest that this cohort of team sport athletes suffer a preponderance of poor sleep quality, with associated high levels of daytime sleepiness. Athletes should receive education about how to improve sleep wake schedules, extend total sleep time and improve sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
6
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 46 publications
8
95
6
6
Order By: Relevance
“…Mild sleep-disordered breathing has been found to occur in 8% of college American footballers76 and 19% of professional American footballers 114. One in four professional ice hockey players has significant problems sleeping,77 while a study examining rugby and cricket players found 38% defined themselves as snorers 115. Athletes with high body mass index, large neck circumference or high levels of adiposity may be at a heightened risk of developing a sleep disorder 76 114.…”
Section: Discussionmentioning
confidence: 99%
“…Mild sleep-disordered breathing has been found to occur in 8% of college American footballers76 and 19% of professional American footballers 114. One in four professional ice hockey players has significant problems sleeping,77 while a study examining rugby and cricket players found 38% defined themselves as snorers 115. Athletes with high body mass index, large neck circumference or high levels of adiposity may be at a heightened risk of developing a sleep disorder 76 114.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, a small but notable number of athletes was identified with ‘restless leg symptoms’ (RLS/PLMD). The current prevalence of potential sleep disorders compares with the general population and is in accordance with previous findings among athletes (Swinbourne et al ., ; Tuomilehto et al ., ), thereby highlighting the need for sleep monitoring and potentially treatment of sleep disorders in elite athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that elite athletes have poor sleep quality [9,[15][16][17]. For example, more than 55% of athletes in the Bobsleigh Canada Skeleton team were flagged as being poor sleepers [9].…”
Section: Introductionmentioning
confidence: 99%